2008
DOI: 10.1111/j.1574-6941.2008.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Coaggregation between and among human intestinal and oral bacteria

Abstract: Coaggregation is believed to facilitate the integration of new bacterial species into polymicrobial communities. The aim of this study was to investigate coaggregation between and among human oral and enteric bacteria. Stationary phase cultures of 10 oral and 10 enteric species, chosen on the basis of numerical and ecological significance in their respective environments together with their ease of cultivation, were tested using a quantitative spectrophotometric coaggregation assay in all possible pairwise com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…Mucin is a glycosylated protein and attachment of bacteria to mucin involves specific bacterial proteins such as mucus-binding proteins and other lectins or adhesins. A majority of the aggregation interactions between gut isolates are mediated by lectin-carbohydrate interaction (Ledder et al, 2008). In Lactobacillus reuteri strains, mucus binding showed excellent correlation with the presence of cell-surface mucus-binding protein and was further highly associated with the autoaggregation properties of Lb.…”
Section: Discussionmentioning
confidence: 89%
“…Mucin is a glycosylated protein and attachment of bacteria to mucin involves specific bacterial proteins such as mucus-binding proteins and other lectins or adhesins. A majority of the aggregation interactions between gut isolates are mediated by lectin-carbohydrate interaction (Ledder et al, 2008). In Lactobacillus reuteri strains, mucus binding showed excellent correlation with the presence of cell-surface mucus-binding protein and was further highly associated with the autoaggregation properties of Lb.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies showed that bacteria from different origins were less likely to have direct physical binding as revealed by coaggregation assay [27]. Using BHI cultivated mice gut microbial community [20] we further tested the interbacterial binding between oral species and gut flora.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies employing the standard coaggregation assay have shown that bacteria from different microbial communities exhibit less interbacterial binding than species originating from the same community [27]. Therefore, we investigated the co-adherence profiles of F. nucleatum and S. mutans with a foreign flora using cultivated mice gut flora as a model community.…”
Section: Oral Bacterial Species Displayed Less Co-adherence With Micementioning
confidence: 99%
“…From this observation, the aggregation of L. brevis in response to xylan was not considered to involve a specific reaction mediated by proteins, such as lectin-like proteins, which were previously identified as factors for the aggregation and gastrointestinal tract adherence of Lactobacillus. 8,9,[12][13][14][15]23) However, another type of protein was considered to mediate xylan-induced aggregation based on the effects of pH and temperature on aggregation.…”
Section: )mentioning
confidence: 99%
“…8,9) LAB strains belonging to Lactobacillus brevis and Lactobacillus gasseri that recognize human blood type-A antigen through recognition of the sugar chain of the antigen were reported. 10,11) Mannose-specific adhesion to the porcine jejunal epithelium by Lactobacillus plantarum 12) and coaggregation between and among human intestinal and oral bacteria via lectin-carbohydrate interactions 13) have also been reported. Furthermore, the aggregation of LAB and yeast cells mediated by mannose and/or mannan in the yeast cell wall has been confirmed for L. plantarum 14,15) and Lactococcus lactis.…”
mentioning
confidence: 99%